2013
DOI: 10.1155/2013/264046
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Temperature, Relative Humidity and Seasonal Variability on Ambient Air Quality in a Coastal Urban Area

Abstract: The concentration of air pollutants in ambient air is governed by the meteorological parameters such as atmospheric wind speed, wind direction, relative humidity, and temperature. This study analyses the influence of temperature and relative humidity on ambient SO2, NOx, RSPM, and SPM concentrations at North Chennai, a coastal city in India, during monsoon, post-monsoon, summer, and pre-monsoon seasons for 2010-11 using regression analysis. The results of the study show that both SO2 and NOx were negatively co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
78
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(94 citation statements)
references
References 8 publications
14
78
1
1
Order By: Relevance
“…In their paper titled "Influence of Temperature, Relative Humidity and Seasonal Variability on Ambient Air Quality in a Coastal Urban Area", Jayamurugan, R., Kumaravel, B., Palanivelraja, S., & Chockalingam, M. P. establish a correlation between ambient atmospheric temperature and concentrations of greenhouse gases [7]. The conclusion reached in their paper agrees with the results derived here through analysis of lidar data, such as NRB and NRB error.…”
Section: Resultssupporting
confidence: 77%
“…In their paper titled "Influence of Temperature, Relative Humidity and Seasonal Variability on Ambient Air Quality in a Coastal Urban Area", Jayamurugan, R., Kumaravel, B., Palanivelraja, S., & Chockalingam, M. P. establish a correlation between ambient atmospheric temperature and concentrations of greenhouse gases [7]. The conclusion reached in their paper agrees with the results derived here through analysis of lidar data, such as NRB and NRB error.…”
Section: Resultssupporting
confidence: 77%
“…We first estimated models with only the regional dependent variable, and then in subsequent models added weather variables as covariates. Weather variables were considered because of the possible effects of these variables on pollutant levels . We conducted a sensitivity analysis that excluded days with humidity >95%.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, temperature can affect NO 2 negatively in two ways: firstly through direct effect by enhancing the photo-dissociation; and secondly through affecting other meteorological parameters, such as wind speed and atmospheric stability to enhance the dispersion process. Jayamurugan et al (2013) have also reported negative association between temperature and NO 2 , stating that heating of earth by the sun induces thermal turbulence during summer and increases the mixing height and therefore help increase the dispersion process of NO 2 . Therefore, it seems likely that reduction in the levels of NO 2 and THCs at extremely high temperature are causing ozone level to decrease and is the likely reason of the negative ozone-temperature slopes at extremely high temperature.…”
Section: Resultsmentioning
confidence: 99%